2020
DOI: 10.1108/mf-11-2019-0579
|View full text |Cite
|
Sign up to set email alerts
|

Underwriter reputation and IPO valuation in an emerging market: evidence from Malaysia

Abstract: PurposeThe purpose of this study is to examine the influence of underwriter reputation on the valuation of Malaysian initial public offerings (IPOs).Design/methodology/approachThis study employed cross-sectional multiple regression models to analyse the relationship between underwriter reputation and IPO valuation that included 466 IPOs listed on Bursa Malaysia from 2000 to 2017.FindingsThe results revealed that underwriter reputation had a significant negative association with IPO valuation. Firms that engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
1
14
1
1
Order By: Relevance
“…Initial studies by Beatty & Ritter [26], Johnson & Miller [27], Carter & Manaster [28], Carter, Dark, & Singh, [29], Aggarwal [30], Kirkulak-Uludag and Davis [31] have shown that prestigious underwriters reflect firm competence and thus contribute to low first-day returns in the secondary markets. Recent studies by Widarjo et al [32], Angelia and Basana [33], Albada, Low and Yong [18], Rumokoy et al [17], and Ong, Mohd-Rashid, and Taufil-Mohd [19], using Malaysian and Indonesian data respectively, further supports the inverse relationship between underwriters reputation and first-day initial returns. Contrary to the above, studies by Beatty and Welch [34]; Cooney et al [35]; Bates and Dunbar, [36]; Loughran & Ritter, [37] document a positive relationship, whereby while respectable underwriters still reflect firm efficiency, investors see it as an incentive to raise their demand for IPOs in the secondary market, prompting prices to surge upwards and thus a higher returns on these IPOs.…”
Section: Underwriters' Reputationmentioning
confidence: 70%
See 3 more Smart Citations
“…Initial studies by Beatty & Ritter [26], Johnson & Miller [27], Carter & Manaster [28], Carter, Dark, & Singh, [29], Aggarwal [30], Kirkulak-Uludag and Davis [31] have shown that prestigious underwriters reflect firm competence and thus contribute to low first-day returns in the secondary markets. Recent studies by Widarjo et al [32], Angelia and Basana [33], Albada, Low and Yong [18], Rumokoy et al [17], and Ong, Mohd-Rashid, and Taufil-Mohd [19], using Malaysian and Indonesian data respectively, further supports the inverse relationship between underwriters reputation and first-day initial returns. Contrary to the above, studies by Beatty and Welch [34]; Cooney et al [35]; Bates and Dunbar, [36]; Loughran & Ritter, [37] document a positive relationship, whereby while respectable underwriters still reflect firm efficiency, investors see it as an incentive to raise their demand for IPOs in the secondary market, prompting prices to surge upwards and thus a higher returns on these IPOs.…”
Section: Underwriters' Reputationmentioning
confidence: 70%
“…In a mature capital market with robust legal structures and investor protections, high ownership further solidifies the collaborations as it reduces insider information, thereby boosting investor confidence in firm credibility. The relationship eventually induces a rise in demand for IPOs in the secondary market, thus leading to favorable first-day returns as reported by Allen and Faulhaber [6], Grinblatt and Hwang [40], Welch [7], Datar, Felthan and Hughes [13], Titman and Trueman [12], Loughran & Ritter [37], Rumokoy et al [17], Albada, Low and Yong [18] and Ong, Mohd-Rashid and Taufil-Mohd [19]. As noted earlier, the civil law nation has a comparatively weaker legal system, investor protection, and enforcement of rules and regulations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Studies document a negative correlation between underpricing and reputation, whether of underwriters or auditors (Albada et al, 2019a(Albada et al, , 2019bD. Sundarasen, 2019;Kaur and Singh, 2019;Kenourgios et al, 2007;Ong et al, 2020;Pratoomsuwan, 2012). Issuers seem to accept the costs of hiring reputable underwriters or auditors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%